Bacillus velezensis R22 inhibits the growth of multiple fungal phytopathogens by producing surfactin and four fengycin homologues - Nadya Armenova; Penka Petrova; Maria Gerginova; Ekaterina Krumova; Dimitar Kaynarov; Lyudmila Velkova; Pavlina Dolashka; Kaloyan Petrov (Biotechnology & Biotechnological Equipment)
Significant agricultural losses are caused by the phytopathogenic fungi Botrytis cinerea and Phytophthora infestans, as well as bacteria of the Ralstonia solanacearum species. The present work aimed to isolate rhizobacteria for simultaneous biocontrol of these three phytopathogenic species and to suggest the mechanisms of their antagonistic action. Among 120 Bacillus spp. isolated from soils, Bacillus velezensis and Bacillus licheniformis strains displayed the highest activity against all three phytopathogens. A rapid, polymerase chain reaction-based method for detecting nonribosomal peptide synthetase genes was developed to elucidate the genetic basis of these traits. The presence of fenA, srfAA, ppsA, and lchAA genes, encoding fengycin/surfactin/plipastatin synthetases and lichenysin synthase, was revealed in the strains’ genomes. The whole genome sequencing (WGS) of B. velezensis R22 showed that it contains 4,081,504 bp (with G + C content 46.35%), 4087 genes for 3935 proteins, 72 tRNAs, 14 rRNAs, and 5 ncRNAs. WGS allowed the prediction of 10 complete clusters for secondary metabolites with putative antimicrobial activity: difficidin, fengycin, bacillaene, butyrosin, bacillibactin, bacilysin, surfactin, macrolactin H, macrolactin R22, and velezensin. LC-MS and high-sensitivity UHPLC-Q-TOF LC-MS/MS analysis were used to search for the predicted metabolites in cell-free supernatants of B. velezensis R22. The compounds with the strongest antifungal activity are surfactin with a C15 β-OH fatty acid chain; two homologous forms of fengycin A; and two fengycin B homologues containing C16 and C17 β-hydroxy fatty acid chains. The broad antimicrobial spectrum of B. velezensis R22 and its molecular characterization provide a good basis for the future development of plant protection preparations.